Assessing information system readiness for mitigating malpractice risk through simulation: results of a multi-site study. (26th May 2015) - Wright, Adam; Maloney, Francine L; Wien, Matthew; Samal, Lipika; Emani, Srinivas; Zuccotti, Gianna
Abstract: Objective To develop and test an instrument for assessing a healthcare organization's ability to mitigate malpractice risk through clinical decision support (CDS). Materials and Methods Based on a previously collected malpractice data set, we identified common types of CDS and the number and cost of malpractice cases that might have been prevented through this CDS. We then designed clinical vignettes and questions that test an organization's CDS capabilities through simulation. Seven healthcare organizations completed the simulation. Results All seven organizations successfully completed the self-assessment. The proportion of potentially preventable indemnity loss for which CDS was available ranged from 16.5% to 73.2%. Discussion There is a wide range in organizational ability to mitigate malpractice risk through CDS, with many organizations' electronic health records only being able to prevent a small portion of malpractice events seen in a real-world dataset. Conclusion The simulation approach to assessing malpractice risk mitigation through CDS was effective. Organizations should consider using malpractice claims experience to facilitate prioritizing CDS development.